2022
DOI: 10.3390/ijms232012533
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Droplets in Lung Cancers Are Crucial for the Cell Growth and Starvation Survival

Abstract: For rapid and unlimited cell growth and proliferation, cancer cells require large quantities of nutrients. Many metabolic pathways and nutrient uptake systems are frequently reprogrammed and upregulated to meet the demand from cancer cells, including the demand for lipids. The lipids for most adult normal cells are mainly acquired from the circulatory system. Whether different cancer cells adopt identical mechanisms to ensure sufficient lipid supply, and whether the lipid demand and supply meet each other, rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(36 reference statements)
0
6
1
Order By: Relevance
“…8 ). However, we did not observe intracellular lipid droplets, presumably because of increased lipid utilization for cell growth, proliferation, migration, invasion and cell survival of cancer cells 44 , 45 . This could also explain the increased EMT of the TNBC cells.…”
Section: Discussioncontrasting
confidence: 71%
“…8 ). However, we did not observe intracellular lipid droplets, presumably because of increased lipid utilization for cell growth, proliferation, migration, invasion and cell survival of cancer cells 44 , 45 . This could also explain the increased EMT of the TNBC cells.…”
Section: Discussioncontrasting
confidence: 71%
“…1 f) contrary to immunocytes (Fig. 1 G), and we speculate that PLIN3 was as important as LDs for the growth of tumor cells, but also indispensable for immune cells in the activation of CD8 + T lymphocytes [ 32 , 33 ]. There was no significant link between PLIN3 and Ki-67 in OSCC fibroblasts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PLIN3 also appears to play a significant role in cancer pathogenesis. Studies have reported abnormal PLIN3 expression in several types of cancer, including cervical [128], clear cell renal cell [129], breast [93], lung [130], and prostate [131][132][133]. The prevalence of high PLIN3 levels in these cancer types could suggest an increased rate of LD biogenesis or potentially hindered conditions for PLIN3 s CMA.…”
Section: Perilipinmentioning
confidence: 99%